2012
DOI: 10.1103/physrevx.2.011002
|View full text |Cite
|
Sign up to set email alerts
|

Rectification at Graphene-Semiconductor Interfaces: Zero-Gap Semiconductor-Based Diodes

Abstract: Using current-voltage (I-V), capacitance-voltage (C-V), and electric-field-modulated Raman measurements, we report on the unique physics and promising technical applications associated with the formation of Schottky barriers at the interface of a one-atom-thick zero-gap semiconductor (graphene) and conventional semiconductors. When chemical-vapor-deposited graphene is transferred onto n-type Si, GaAs, 4H-SiC, and GaN semiconductor substrates, there is a strong van-der-Waals attraction that is accompanied by ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
224
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(246 citation statements)
references
References 24 publications
18
224
4
Order By: Relevance
“…Unusual properties of graphene promising for a variety of novel applications [23][24][25][26][27][28] have also triggered significant interest in one or several atom-thick honeycomb structures of binary compounds. Early experimental studies aiming to synthesize and characterize novel monolayer materials have revealed that graphene-like sheets of BN are also stable.…”
Section: Introductionmentioning
confidence: 99%
“…Unusual properties of graphene promising for a variety of novel applications [23][24][25][26][27][28] have also triggered significant interest in one or several atom-thick honeycomb structures of binary compounds. Early experimental studies aiming to synthesize and characterize novel monolayer materials have revealed that graphene-like sheets of BN are also stable.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum on Oxide-1 shows a single 2D peak larger than the G peak, a clear sign of single layer graphene. 5,20 The spectrum on Zn 3 P 2 has the same characteristics but with lower signal intensity. The data indicates that we have single layer graphene on our substrate.…”
mentioning
confidence: 95%
“…These limitations can be addressed using graphene, which has previously been used to form graphene−semiconductor junctions 5 and solar cells with CdS and CdSe 6,7 semiconductors as well as with Si,5,[8][9][10][11] demonstrating Schottky barrier behavior. 5 Further advances on graphene−semiconductor junctions were demonstrated by building gate-controlled devices in order to modify the Schottky barrier height and the electrical transport across the junction. This design has been used to build a graphene−Si transistor (barristor) 12 and a graphene−organic thin film junction transistors.…”
Section: Introductionmentioning
confidence: 99%
“…∆Φ B (V ) is typically dominant in reverse bias because of the higher potential drop on the Schottky junction, resulting in a more pronounced barrier-lowering Schottky effect [8,61] and SLG Fermi level shift [37,38,61]. On the other hand, in forward bias the potential drop is limited by the built-in voltage (V bi <1V) [8], so that ∆Φ B (V ) can be neglected and Φ B ∼ Φ B0 .…”
Section: Introductionmentioning
confidence: 99%